Effects of different extenders, cryoprotectants, equilibration and vapour exposure on freezability of African catfish(Clarias gariepinus) sperm / Noor Azlina Kamaruding - Kamaruding, Noor Azlina (2010)
The aim of this study was to develop an optimal freezing protocol for African catfish(Clarias gariepinus) sperm with special reference to type of extender and cryoprotectant, molarity, equilibration duration, vapour temperature and vapour exposure duration. Using Tris-Citric Acid Yolk Extender (TCAYE), a 3x3x3x3 factorial experiment was carried out consisting of 3 molarities of glycerol (0.5, 1.0 and 2.0 M), 3 equilibration durations (120,140 and 160 minutes), 3 vapour temperatures (-80, -90 and -100oC) and 3 vapour exposure durations (5, 10 and 15 minutes). In addition, using Fish-Ringer Extender (FRE), a 3x3x3 factorial experiment was also conducted involving 3 equilibration durations (120, 140 and 160 minutes), 3 vapour temperatures (-80, -90 and -100oC) and 3 vapour exposure durations (5, 10 and 15 minutes). The molarity of cryoprotectant in FRE extender was fixed at 10% DMSO. Briefly, the straws containing the sperm were placed in refrigerator at 4oC with the fixed equilibration duration after which exposed to liquid nitrogen vapour at the fixed vapour temperature with the fixed vapour exposure duration. Subsequently, the straws were directly plunged into liquid nitrogen. The frozen sperm were thawed at 30oC for 30 seconds to evaluate the sperm motility characteristics using the automated semen analyzer (IVOS; Hamilton Thorne, USA). The effects of factors and parameters measured were analysed using Analysis of Variance (ANOVA) followed by Duncan Multiple Range Test (DMRT). In Experiment 1, large body weight (BW) of African catfish gave the highest fresh sperm total motility (82.40±4.59%) followed by medium BW (51.64±9.82%) and small BW (40.40±12.16%), whereby small BW fish were significantly different in total motility compared with the other two groups studied. In Experiment 2, glycerol with molarity of 0.5 M showed significantly the highest value of frozen-thawed sperm total motility (32.27±2.05%) as compared to 1.0 M (24.50±1.81%) and 2.0 M (2.63±0.29%). At 140 minutes equilibration duration, the value of total motility (31.69±2.19%) was 24 significantly higher as compared to 120 minutes (25.26±1.76%). There were no significant differences (P>0.05) in value of total motility for -80, -90 and -100oC which were ranged from 25.95±2.34% to 29.41±1.69%. The value of total motility did not show any significant differences (P>0.05) among the three vapour exposure durations (5, 10 and 15 minutes), which were ranged from 27.63±2.02% to 28.45±2.14%. In Experiment 3, there were no significant differences (P>0.05) in values of total motility at 120 minutes(76.65±2.27%) and 160 minutes equilibrations (76.01±2.04%), but these durations gave comparatively higher values of total motility than 140 minutes (66.90±2.60%). The values of total motility for vapour temperatures of -90oC (74.07±2.02%) and -100oC (74.95±1.88%) did not show any significant differences (P>0.05), but they were significantly different with -80oC, which gave comparatively lower values (64.59±5.08%).There were no significant differences (P>0.05) in values of total motility for 5, 10 and 15 minutes which were ranged from 72.67±2.27% to 73.99±2.34%. In Experiment 4, there were no significant differences (P>0.05) for values of total motility between 1.0 M(24.50±1.81%) and 2.0 M of glycerol in TCAYE (26.74±2.14%), but they were comparatively lower than 0.5 M of glycerol that showed higher significant value(32.27±2.05%). On the other hand, combination of DMSO (10%) in FRE extender showed the highest significant value of total motility (73.52±1.35%) as compared to the three molarities of glycerol in TCAYE extender. In summary, the best combination to obtain the highest frozen-thawed sperm motility characteristics for TCAYE extender was 0.5 M of glycerol, 140 minutes equilibration duration, -90oC vapour temperature and 5 to 15minutes vapour exposure duration, whereas for FRE extender was 120 minutes equilibration duration, -100oC vapour temperature and 5 to 15 minutes vapour exposure duration. In conclusion, results obtained in this study showed that 10% DMSO with FRE extender produced higher frozen-thawed sperm total motility than TCAYE extender.25 Future studies are needed through refinement in factors involved during freezing process that influence sperm survival before it can be used routinely in the reproduction of African catfish (Clarias gariepinus).